2002
DOI: 10.1021/jf020462r
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Inactivation of Pectin Methylesterase, Polygalacturonase, and Peroxidase in Tomato Juice

Abstract: Thermal inactivation kinetics have been determined for pectin methylesterase (PME), polygalacturonase (PG), and peroxidase (POD) in tomato juice. Two parameters, the inactivation rate constant (k) at a reference temperature and the activation energy for inactivation (E(a)), were determined for each enzyme. For PME and PG, the k and E(a) values reported here do not agree with those in several previously published reports. These differences can be explained either by the differences in pH values used for inactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1
16

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(83 citation statements)
references
References 18 publications
4
61
1
16
Order By: Relevance
“…PPO and POD in Granada clingstone peaches showed this behavior (Toralles et al, 2004). Anthon et al (2002) also observed such behavior in pectin methyl esterase in tomato juice. At 70 °C, 95% of the PPO activity was lost after 540 seconds, and similar loss was observed after incubation at 90 °C for about 60 seconds, suggesting that PPO catalytic structure was significantly changed when temperature increased.…”
Section: Decimal Reduction Time (D-value)mentioning
confidence: 65%
“…PPO and POD in Granada clingstone peaches showed this behavior (Toralles et al, 2004). Anthon et al (2002) also observed such behavior in pectin methyl esterase in tomato juice. At 70 °C, 95% of the PPO activity was lost after 540 seconds, and similar loss was observed after incubation at 90 °C for about 60 seconds, suggesting that PPO catalytic structure was significantly changed when temperature increased.…”
Section: Decimal Reduction Time (D-value)mentioning
confidence: 65%
“…Firmeza da polpa (A) e perda de massa de matéria fresca (B), em frutos de camu-camu colhidos em quatro estádios de maturação -1, verde; 2, verde-avermelhado; 3, vermelho-esverdeado; e 4, roxo -, armazenados a 22±1°C e 85±5% UR, durante 12 dias. como a poligalacturonase e pectinametilesterase, que promovem intensa solubilização das pectinas, constituintes da parede celular, o que resulta em perda de firmeza (Anthon et al, 2002;Silva et al, 2009). O ângulo de cor e as coordenadas de cromaticidade a* e b* expressaram com exatidão as diferenças na coloração da casca dos camu-camus e permitiram uma visualização precisa da mudança de cor após a colheita (Tabela 1).…”
Section: Resultsunclassified
“…Duas principais enzimas estão envolvidas no processo de amaciamento dos frutos, a poligalacturonase (PG) e a pectinametilesterase (PME) (ANTHON et al, 2002).…”
Section: Resultsunclassified